AMAND BINEAU - Jaime Wisniak (Revista CENIC Ciencias Químicas, 2021)
Amand Bineau (1812-1856), a French chemist who determined the density of a large number of gases and vapors and assumed that the anomalies were due to molecular aggregates. The influence of the distance between molecules was negligible compared to the influence of the temperature. Justification of abnormal densities using equivalent values required assuming that the molecules of the gas were not acting independently but as groups. In the case of acetic acid the concordance between observed density and equivalents occurred only if the molecules were paired as a dibasic acid. Bineau studied the phenomenon of azeotropy in aqueous solutions of hydrogen chloride and determined that it occurred at the composition of 1 equivalent of acid and 16 of water. He determined the composition of nitrogen halogens by determining the ratio between its elements and studied the reaction of ammonia with a variety of reagents, among them hydrogen sulfide, selenhydric and telluric acids and ammonium halocyanates, as well as the isomerism of the latter. He developed a series of analytical techniques for nitrogen, ammonia, carbon dioxide, magnesium, and calcium carbonate and studied the effect of nitrogen and ammonia on the growth of algae